Digital transformation and its impact on improving environmental services – An applied study on the Ministry of Environment and Agriculture, Jeddah province – - Alharthi, Thyab Abdullah; Asfora, Evan (Journal of Economic, Administrative and Legal Sciences, 2020)
The research aims to: Identify the efforts of the Ministry of Environment and Agriculture to make digital transformation, also to identify the obstacles on digital transformation in the ministry, and identify practices and standards for digital transformation, and to reveal the excellence in providing service to beneficiaries in the ministry. The researcher used the descriptive analytical method. The study population consisted of the workers in the Ministry of Environment and Agriculture. The sample size was (60) individuals. Results of the research came as follows: There are obstacles in the Ministry of Environment and Agriculture which is prevent the application of the digital transformation, and that was on average (3.66).Also there were efforts exerted by the Ministry towards digital transformation, with an average of (3.68), there is a distinction in providing service to beneficiaries in the Ministry as a result of applying the digital transformation with an average of (3.57), that the beneficiaries do not have sufficient knowledge of electronic transactions and computer software, where the average (2.38).Recommendations reached by the study: Work to intensify efforts at the Ministry of Environment towards digital transformation. The necessity of identifying the obstacles that prevent the application of the digital transformation and working to solve its, which include: working to ensure confidentiality of data and protecting them from internal and external risks, the need to train employees of the ministry on electronic programs and applications for digital transformation and keep abreast of all new programs and technologies.
Keywords: transformation; digital transformation; upgrading services; environment